Orbital Cyst with Ependymal Differentiation Associated with Microphthalmia. (4th March 2022) - Garcia, Maria D.; Salomao, Diva R.; Wagner, Lilly H.
Abstract: Background Orbital cysts associated with microphthalmia are colobomatous lesions that typically present unilaterally and posterior to the globe. Case Report: A male infant had an orbital cyst associated with microphthalmia located anterior to the globe composed of a neuroglial wall, ependymal-like epithelial lining, with synaptophysin-positive cells resembling the retinal neuronal layer. Conclusion: This orbital cyst may represent a malformation of the eye rather than an encephalocele.